Usefulness of Adalimumab in the Treatment of Refractory Uveitis Associated with Juvenile Idiopathic Arthritis - Carmen García-De-Vicuña; Manuel Díaz-Llopis; David Salom; Rosa Bou; Jesus Díaz-Cascajosa; Miguel Cordero-Coma; Gabriela Ortega; Norberto Ortego-Centeno; Marta Suarez-De-Figueroa; Juan Cruz-Martínez; Alex Fonollosa; Ricardo Blanco; et al. (Mediators of Inflammation)
Purpose. To assess the efficacy and safety of adalimumab in patients with juvenile idiopathic arthritis (JIA) and associated refractory uveitis. Design. Multicenter, prospective case series. Methods. Thirty-nine patients (mean [SD] age of 11.5 [7.9] years) with JIA-associated uveitis who were either not responsive to standard immunosuppressive therapy or intolerant to it were enrolled. Patients aged 13–17 years were treated with 40 mg of adalimumab every other week for 6 months and those aged 4–12 years received 24 mg/m2 body surface. Results. Inflammation of the anterior chamber (2.02 [1.16] versus 0.42 [0.62]) and of the posterior segment (2.38 [2.97] versus 0.35 [0.71] decreased significantly between baseline and the final visit (P<0.001). The mean (SD) macular thickness at baseline was 304.54 (125.03) μ and at the end of follow-up was 230.87 (31.12) μ (P<0.014). Baseline immunosuppression load was 8.10 (3.99) as compared with 5.08 (3.76) at the final visit (P<0.001). The mean dose of corticosteroids also decreased from 0.25 (0.43) to 0 (0.02) mg (P<0.001). No significant side effects requiring discontinuation of therapy were observed. Conclusion. Adalimumab seems to be an effective and safe treatment for JIA-associated refractory uveitis and may reduce steroid requirement.